2010
DOI: 10.1089/jpm.2010.0128
|View full text |Cite
|
Sign up to set email alerts
|

What Factors Are Important in Increasing Junior Doctors' Willingness To Provide Palliative Care in Taiwan? An Educational Intervention Study

Abstract: Educating junior doctors to build positive beliefs toward palliative care is strongly encouraged. Palliative care education contributes to increased junior doctors' willingness toward providing palliative care, which suggests that this kind of training course should be emphasized in medical education.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 32 publications
(31 reference statements)
1
8
0
Order By: Relevance
“…Learning palliative care through medical school education might enhance physicians' positive attitudes to provide care for terminal cancer, presenting correct concepts and knowledge of palliative care. This finding was resemble to study in Taiwan which revealed that junior doctors were strongly encouraged to have correct principles of palliative care and develop positive attitudes toward palliative terminal care by educating in medical program (Shih et al, 2010).…”
Section: Discussionsupporting
confidence: 72%
“…Learning palliative care through medical school education might enhance physicians' positive attitudes to provide care for terminal cancer, presenting correct concepts and knowledge of palliative care. This finding was resemble to study in Taiwan which revealed that junior doctors were strongly encouraged to have correct principles of palliative care and develop positive attitudes toward palliative terminal care by educating in medical program (Shih et al, 2010).…”
Section: Discussionsupporting
confidence: 72%
“…A recent study of the willingness of junior clinicians in Taiwan to provide palliative care indicates that educational intervention regarding end-of-life care is highly needed among health care personnel in Taiwan and the training course of palliative care should be emphasized earlier in medical education. 28…”
Section: Discussionmentioning
confidence: 99%
“…All articles indicated improvements in student knowledge, attitudes, and/or preparedness to practice palliative care concepts compared to no intervention. 5,6,19,42 93 Most articles used pretest/posttest surveys or qualitative analysis of student reflections to evaluate the teaching intervention. Only 1 article was identified that evaluated several different teaching methods against a control to assess optimal strategy for teaching regarding cancer pain.…”
Section: Resultsmentioning
confidence: 99%